Mandailing And Angkola Semarga Marriage; Comparative Study Of Polemic Custom Law And Positive Law In Indonesia - Affandi, Hazrul; Ritonga, Hasir Budiman; Ritonga, Raja (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2023)
Marriage is part of realizing maqashid sharia, namely maintaining the continuity of offspring Traditional marriages in the Mandailing and Angkola communities have special values and rules. Customary violations can result in sanctions and fines from customary leaders. This article examines the polemic of semarga marriage among the Mandailing and Angkola tribes in the review of customary law and positive law in Indonesia. This research is qualitative research with a type of field research. Primary data collection is done through observation, interviews, and documentation. Meanwhile, secondary data is collected by tracing many references from books, articles, and other scientific works that are related to the research theme. Furthermore, the data were analyzed descriptively with a legal or normative approach. The results of the study explain that the same clan marriage in the Mandailing and Angkola ethnic communities has significant differences. Semarga marriages in the Angkola community are not subject to customary sanctions and fines. Meanwhile, semarga marriages in the Angkola community are subject to customary sanctions and fines. Meanwhile, the review of the Compilation of Islamic Law or positive law states that marriages are prohibited if marriages are carried out with mahrams or people who are prohibited from marrying.